Self-healing scleredema. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Scleredema is a rare disorder, even more rare in children (2). Histologically, it differs from scleroderma due to the presence of adnexa and of large interfibrous spaces containing acid mucopolysaccharides. Clinically, it differs from scleroderma due to its sudden onset, sometimes after an infection (3). Also its healing can be very rapid (1) as in our case. Moreover, skin involvement in scleredema is more diffuse and prevails on the trunk and root of the limbs, although the head, forearms and hands can be affected. In scleredema the borders of the lesions are not well defined as compared with scleroderma. Above all in scleredema the skin is normally colored without erythema and porcelain-like sclerosis and, in case of healing, the skin does not show dyschromic residua.